Microfinance, EU Structural Funds and Capacity Building for Managing Authorities A Comparative Analysis of European Convergence Regions - Porretta, Pasqualina; Pes, Giovanni (Palgrave Studies in Impact Finance,, 2016)
In recent years, the European Commission has attached increasing importance to the use of financial engineering instruments rather than traditional grant-based financing for the microcredit sector, considering these to be the most efficient option available. This book presents a study of capacity building and structural funds in public managing authorities for the microcredit sector. It presents two surveys to highlight the strengths and weaknesses of the managing authorities' capacity building. The first survey investigates the authorities' need for and interests in capacity building activities, assessing the areas in which capacity building support is needed, and explores the different types of support offered. The second survey analyses the results of the microcredit and microfinance programming activity, investigating its target groups and other operational features. It examines the key monitoring and reporting issues involved in this activity, before analysing the regulatory framework of the microcredit and microfinance sector. This book presents an in-depth analysis of structural funds and their management by policy-makers in the European convergence regions. It explores the interests of managing authorities, microcredit institutions, operators and other financial intermediaries involved in microcredit programming activities, and offers some core strategic and operational recommendations for the use of structural funds in the microcredit sector.